UNDERSTANDING SOCIAL STIGMA RELATED TO RELIGION AND WOMEN IN INDIA AND IDENTIFYING WAYS TO PROMOTE DEMOCRACY - Ghosh, Baijayanti (ShodhKosh: Journal of Visual and Performing Arts, 2021)
The study has tried to connect social stigma and religion that exist in India especially among women causing their distress. Indian women suffer from discrimination in all places that restricts their contribution to society. The research has highlighted that Christian groups of women expressed a feeling of suppression and discrimination by 30% in a survey of 2020. The POSH Act fails to address the social injustice that religious scriptures impose on this patriarchal society. Thus, a secondary qualitative study has been conducted to critically examine the factors influencing social stigma and causes of insufficient democracy in India.